Labour Remuneration in Public Health System in Time of Digital Transformation of Medical Services - A. M. Chililov; F. N. Kadyrov; O. V. Obuhova (Вестник Российского экономического университета имени Г. В. Плеханова)
Different aspects of using tele-medical technologies recognized as one of key lines in the development of the advanced public health system are highlighted more and more widely in academic literature. However, prospects of this trend depend not only on progress in the development of medical and information technologies and finance investment in the sphere, but also on economic interest in it on the part of concrete medical workers and it can be directly connected with remuneration systems of workers who render tele-medical services. During the research the authors identified key factors that influence on labour remuneration of workers, who participate in tele-medical technologies. Situations of rendering medical aid were classified in view of the following criteria: time, when telemedical services are to be used (principle and extra); whether the job is included in the job description of a concrete worker; whether remuneration components affect the basic pay of the worker, etc. The authors put forward methodological approaches to working out systems of remuneration aimed at the development of tele-medical technologies by state power bodies and public health institutions.